(untitled) (Research, Society and Development, 2021)
According to the Brazilian Society of Nephrology (SBN) in 2013 Brazil had 50,961 patients undergoing hemodialysis treatment due to CKD. Such data reveal that 5.6% are patients aged 13 to 18 years, although the number is not so significant, there is a gradual development of new cases in children and adolescents, the result of this research serves as a warning for the society. This is an integrative literature review article, using articles from the years 2011 to 2021, excluding theses, dissertations, monographs and non-relevant texts. Chronic kidney disease is a pathology at a critical level, which dialysis treatment is very invasive, causing physical and nutritional limitations and emotional and psychological imbalance.